Trichoderma maomingense (Sordariomycetes, Hypocreaceae), a New Species Isolated From Bamboo in Guangdong Province, China - Dai‐Yan Huang; Qiu‐Rong Huang; Zhang‐Yong Dong; Mei Luo (New Zealand Journal of Botany, 2026)
Trichoderma species are widely distributed across various habitats worldwide and play significant roles in the biological control of plant diseases, plant growth promotion, and soil improvement. In this study, a novel Trichoderma species was isolated from dead culms of Bambusa cerosissima McClure in Maoming City, Guangdong Province, China. Based on morphological characteristics and multigene phylogenetic analyses of translation elongation factor 1 α ( tef1‐α ), nuclear internal transcribed spacer of rDNA region (ITS), and RNA polymerase second largest subunit ( rpb2 ) by both maximum likelihood (ML) and bayesian inference (BI) approaches, three isolates were identified as a new species within the Koningii‐clade, named Trichoderma maomingense sp. nov. The distinctions between this new species and its closely related taxa are discussed in detail.